Evaluation of the mechanical performance of chairs without fasteners constructed of wood–based panels - Diler, Harun; Sapmaz, Taycan Çağdaş; Kasal, Ali; Kuşkun, Tolga; Ceylan, Erkan; Güray, Ersan (Maderas. Ciencia y Tecnología, 2023)
According to the literature review, limited studies were performed related to the production of “without fastener and ready to assemble (RTA)” furniture made of wood-based panel materials with Computer Nu- merical Control (CNC) machines and the evaluation of their strength. The aim of this study was to evaluate the cyclic loading performance of different types of RTA chairs without fastener which produced with CNC machines by using engineering design approach and product engineering methods including performance tests. In the production of chairs, 18 mm thick oriented strand board, medium density fiberboard and Oriental beech plywood were utilized as wood-based panels. Within the scope of the study, 4 different chair types without fasteners were designed and produced, and performance tests were carried out in 3 different loading directions (front to back, back to front and side thrust) with cyclic stepped increasing loading method according to the principles of American Library Association specification. Totally, 108 real size chairs without fastener were prepared and tested. As a result of the study, it was concluded that the chairs produced from Oriental beech plywood gave the best performances, while the chairs produced from medium density fiberboard gave per- formance values close to Oriental beech plywood, except for the side thrust test. However, the mechanical performance values of the chairs constructed of oriented strand board were very low. In conclusion, it could be said that the chairs constructed of Oriental beech plywood and medium density fiberboard without fastener have been found to have sufficient mechanical performance.